Plan de exportación de joyas elaboradas en tagua a las ciudades de provo y salt lake city, Estado Unidos de Norteamerica año 2011 - Tubay Moreira, Máximo Fernando (2011)
This project involves the export of tagua jewelry made in the cities of Provo and Salt Lake City Utah in the U.S. In the process of this plan will export the functions to be performed by three persons, whose names are Johnny Coveña artisan producer and supplier of the product, Preston Carlson Goold single investor and marketer of jewelry to be sent to the U.S. and me Máximo Tubay Moreira entrusted with fulfilling all the formalities of law. The main office is my home located in the city of Quevedo, province of Los Rios in the parish of Prince Nicholas, Fifth Street # 514 and May 24. The export market is the U.S. specifically in the cities of Provo and Salt Lake City Utah cities that have much buying power and a very good infrastructure, with great shopping and above all women who know the jewelry. To make the financial evaluation of the project took into account the income earned in the 3 orders I have made my friend Goold, in which it has invested 100% of the capital, making the project profitable. In the process of this plan which was determined Export are the steps required to run an export of a product from our country to the U.S. using the "Easy Export" of Ecuador's National Post for small and medium export is estimated that the maximum weight should be 30 kilograms (kg) and the dollar price will not exceed $ 5,000 Within this program you can also use EMS service which is an express or immediate delivery which ensures your product to its final destination in a time of no more than 5 days and with all the assurances of the case. For this, the EMS service ensures product traceability from leaving Quevedo (home town), to its final destination in Provo or Salt Lake City, Utah in the U.S.A. Tagua jewelry made, will be sold at retail in the U.S. only Mr. Preston Carlson Goold, among his friends, and recommended. The acquisition of the jewels will be done, by him through a money using money transfer services by DHL or money using one of the services of Banco de Guayaquil (which have no charge for a service free from the company where he works Goold and the national bank) only under the system request This strategic plan also includes the expansion opportunities that arise in the process of marketing of jewelry. The central idea is to work directly with Mr. Goold and implement strategies according to market dynamics and how they will market behaved target or goal. The costs are set in the export process "Easy Export", are determined by the weight of the final product is shipped. This cost will be borne entirely by Mr. Goold, as the trio jewelry (necklace, bracelet and earring), have a net worth, which includes my business gain within In the end, we emphasize the excellent opportunity provided by the government to create "Easy Export" as many formalities pound small microexporters like myself, who see in this business the opportunity to cross borders offering native products quality and enable business growth that also